The Influence of Endorsement on Social Media Instagram on Purchase Interest for Product Lip Cream MakeOver - Trisya Afrilya Suryadi; Krishna Kusumahadi (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2023)
This research aims to determine the decision in purchasing makeover products in which there are ten dimensions consisting of Selebgram, Adolescent Consumptive behavior, Can be trusted, Attractiveness, Skill, Selection of products and brands, Channel Selection, Consumers have different choices, Total purchases, and Payment Method. MakeOver, too, can find the effect of endorsement through Instagram social media on lip cream makeover products. The method used in this study uses quantitative methods with this type of research using descriptive and casual methods. Based on the research strategy used using a questionnaire. The technique used in this study used Impossible Sampling with purposive sampling using a questionnaire with 554 respondents who bought makeover products. Data analysis was carried out in this study using Multiple Linear Regression using SPSS software. Based on the results of the descriptive analysis, the endorsement variable and purchase decision are in a good category. The results of the hypothesis show that celebrity variables, Adolescent Consumptive behavior, Can be trusted, attractiveness, and Skill have a positive and significant relationship to purchase satisfaction either partially or simultaneously. This research is expected to provide benefits and broad insights to other researchers and makeover products regarding the endorsement of satisfaction in purchasing lip cream makeover products. As well as engagement, There is a relationship between endorsement and purchase intention. It is recommended that cosmetic/beauty product makeover companies pay more attention to consumers when buying their products, as this will trigger the success of a product and increase the company's success rate.